Thriving in the gig economy : how to capitalize and compete in the new world of work - McGovern, Marion, 1958- (Career Press, 2017)
Find your place in the gig economy! In the last five years, the world has changed dramatically. Thanks to technology companies like Uber, TaskRabbit, and Instacart, the new gig economy seems to constantly be in the news. But most of the media focus is on the low end of the skill spectrum; little attention is being paid to the best in class professionals who have chosen an independent path. New digital talent platforms are developing at a rapid clip with a wide variety of business models, many catering to very precise, high-value skill sets. You will learn: The difference between the gig economy and the sharing and on demand economies. The best ways to work with digital talent platforms and traditional consulting intermediaries. Commonsense logistics around digital branding, contracts, and employment issues. The tools and services to enhance your practice.